Inovasi E-Modul Matematika Menggunakan CBL Berbasis AR Bernuansa Etnomatematika Jakarta - Puja Ahmad, Khurfatul Jannah Jundiah; Fatra, Maifalinda; Sobiruddin, Dindin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to develop a mathematics e-module using CBL based on Augmented Reality (AR) with Jakarta Ethnomathematics nuances that is valid, able to facilitate students' mathematical critical thinking skills, and get very good responses. The method used was the development method (R&D) with the Plomp model. The Plomp model consists of 3 phases, which are preliminary research, prototype phase, and assessment phase. The results showed that in the preliminary research phase, the results of curriculum analysis, learner needs analysis, and task analysis were obtained so that a solution to improve critical thinking skills could be formulated. In the prototyping phase, an e-module was produced which had an average level of percentage score of material and media validity of 93.44% and 92.31% with “Very Valid” criteria. The posttest results showed that the e-module was able to facilitate students' critical thinking skills seen from the achievement of average completeness which was more than KKTP and classical proportion completeness of more than 75%. Mathematics e-modules using AR-based CBL with Jakarta Ethnomathematics nuances received a “Very Good” response from students of 96.63%. In conclusion, mathematics e-modules using AR-based CBL with Jakarta Ethnomathematics nuances are proven to be categorized as very valid, able to facilitate students' mathematical critical thinking skills, and this module is easy to use in the learning activity. Keywords: Augmented Reality, Challenge Based Learning, Critical Thinking, E-Module, Ethnomathematics